PENCEGAHAN COVID-19 MELALUI INFOGRAFISDI FAKULTAS BAHASA DAN SENI UNESA - Hendro Aryanto; I Nyoman Lodra (Jurnal Dimensi Seni Rupa dan Desain, 2020)
Abstract Corona virus is a new type of coronavirus that is transmitted to humans. This virus can attack anyone, both babies and children,adults, the elderly, pregnant women, and nursing mothers. This viral infection is called Covid-19. Until now, there has not been found a drug or vaccine for prevention.WHO urges people to live side by side with Covid-19 in the future which gives rise to life as “New Normal”. That is humans must always wear a mask when they are outside the house, live clean, always wash their hands with soap and so on. Information through infographics is needed about covid-19 as a reminder and at the same time educating Unesa Faculty of Language and Arts students the importance of maintaining distance, wearing a mask in campus activities to prevent the spread of covid-19. With the existence of an infographic on the prevention of covid-19 at the Faculty of Language and Arts, Unesa hopefully can, raise awareness of all campus members.This infographic was designed considering the lack of information on prevention of Covid-19 at FBS with the target audience of adult adolescents with casual and modern appearance so that the message can be easily understood.Keywords: covid-19, infographics, prevention, design Abstrak Virus Corona adalah jenis baru dari coronavirus yang menular ke manusia. Virus ini bisa menyerang siapa saja, baikbayi,anak-anak, orang dewasa,lansia, ibu hamil, maupunibu menyusui. Infeksi virus ini disebut Covid-19.  SSampai saat ini belum ditemukan obat maupun vaksin untuk pencegahan, WHO menghimbau kedepan manusia harus hidup berdampingan dengan covid-19 yang memunculkan kehidupan dengan sebutan “New Normal” yaitu manusia harus selalu memakai masker jika berada diluar rumah, hidup bersih selalu cuci tangan pakai sabun dan sebagainya. Dibutuhkan sebuah informasi melalui infografis tentang covid-19 sebagai pengingat sekaligus mengedukasi mahasiswa Fakultas Bahasa dan Seni Unesa pentingnya jaga jarak, memakai masker dalam beraktifitas dikampus guna mencegah penyebaran covid-19. Dengan adanya infografis pencegahan covid-19 di Fakultas Bahasa dan Seni Unesa diharapkan dapat, menumbuhkan kesadaran semua civitas kampus. Infografis ini dirancang mengingat minimnnya informasi pencegahan covid-19 di FBS dengan target audiece remaja dewasa berpenampilan casual dan modern sehingga pesan dapat mudah dipahami